(untitled) (The International Research Journal of Management Science, 2023)
Purpose: The main purpose of this study is to determine the different factors that affect the investors risk tolerance in Nepal. Design/Methodology/Approach: In this study, descriptive and causal comparative research design has been used. The present study issued 100 questionnaires to the investors in the NEPSE within Kathmandu Valley, out of which 70 are usable and taken further in this study. Findings: The findings show that demographic factors (age, gender, education and monthly income) and cultural factors (uncertainty avoidance, power distance) are statistically significant with the investor’s risk tolerance. Policy Implications: Young investors are found to be more risk tolerant in this study, and with proper guidance and training to them on stock market, it helps for the stability of the stock market mechanism. Moreover, power distance and uncertainty avoidance are high in Nepal, where investors tend to be under the guidance of their seniors, and invest if they find it worthy enough for them, even if it’s risky. Now, taking this as an opportunity, various relevant training sessions to investors can be done by the board itself in the aspect of ESG Investment, Valuable Investment. Originality/Value: This research adds value by examining factors affecting risk tolerance among Nepali investors, blending demographics and cultural influences. It suggests the potential benefits of guiding young investors and leveraging cultural tendencies toward senior guidance for market stability